CHALLENGES OF LEARNING ENGLISH AS A SECOND LANGUAGE (ESL) - Tulqinova Muxlisa Ibroxim qizi (Scholar Express Journal, 2025)
This article explores the multifaceted challenges faced by learners of English as a Second Language (ESL). It discusses linguistic, cultural, psychological, and educational barriers that hinder effective acquisition of English, supported by literature analysis and empirical observations. The study also suggests pedagogical methods to address these challenges and improve ESL outcomes.
Keywords: English as a Second Language; language learning; cultural barriers; psychological factors